Enteric-coated microencapsulation improves the therapeutic effect of cinnamon oil on artificially infected chicken with Escherichia coli - Huanling Xing; Fang Zhou; Jianhao Lin; Junfeng Ban; Junyi Huang; Xinghai Li; Hanjun He; Yanqun Li; Mei Bai; Xiangxiu Liang; Hong Wu (Poultry Science)
Avian pathogenic Escherichia coli (APEC) is an important bacterial infectious disease can pose a threat to poultry and human health, with infected chicks typically exhibiting diarrhea and enteritis. Cinnamon essential oil (CEO) exhibits significant antibacterial, anti-inflammatory and intestinal regulatory properties but limited bioavailability. This study aims to develop an enteric CEO microcapsule and investigate its regulatory effects on anti-inflammatory, and intestinal microenvironment in E. coli-infected chickens, and to reveal the reasons for its superior therapeutic effect on CEO. Different concentrations of enteric CEO microcapsules and CEO were used to treat artificially infected chicken E. coli models, respectively. Cecal content was collected for 16S rRNA gene sequence analysis and metabonomics. Butyric acid content was detected by gas chromatography-flame ionization detection (GC-FID). Inflammatory factors and lipopolysaccharides (LPS) of serum were measured by corresponding ELISA kits. And inflammatory factors in ileum, jejunum and duodenum tissues were detected via quantitative real-time PCR (qRT‒PCR). Pathologic changes in hepatocytes and duodenum were detected by H&E. Dissolution of enteric CEO microcapsules was determined by the paddle method. We observed that the low-dose CEO microcapsule (APEC+MCL) with at least 75 % lower CEO content increased the bioavailability of CEO. This effect was associated with an improvement in the internal environment of the intestinal tract, as in increasing beneficial bacteria and reducing harmful bacteria. Meanwhile, APEC+MCL significantly increased butyric acid content and restored the gut metabolites, improved the level of intestinal inflammatory factors and reduced the inflammatory response, particularly in the duodenum and jejunum segments, with a significant increase in therapeutic effect. Furthermore, APEC+MCL also improved the levels of TNF-α, IL-1β, IL-6, and IL-10 in serum, as well as the liver's protective effect to reduce mortality and increase feed conversion rate (FCR) and average daily gain (ADG). These findings suggest enteric microcapsule system for CEO significantly enhances CEO's therapeutic potential, offering a promising strategy for developing more efficient and cost-effective natural antibacterial treatments for colibacillosis.